ANDIR AS A SCARED DANCE AT TISATA VILLAGE, KERAMBITAN, TABANAN REGENCY - Arshiniwati, Ni Made (E-Journal of Cultural Studies; Volume 7, Number 3, Agustus 2014, 2014)
Tariandir in the village Tista is a form of Legong Kraton tarisejenis the Tista community called andir.Strukturkoreografinyasangatdekatdengantarilegongkeraton , tetapitari Andir only flourish in the village Tista Kerambitan.Tari inidifungsikan as guardian and bebali art that in the play always involves Rangda sungsungan society , baikditampilkansebagaibagiandariceritamaupunhanyasebagai " witness " pementasannya . Qualitative research by applying the theory of representation , ideology theory , aesthetic theory , and the theory of semiotics examines the main problems that dance andirsebagai sacred art in the village Tista Kerambitan . The results showed that as the art sakraltari Andir related to : ( 1 ) the use of equipment ( sacred objects ) in the form of engagement rangdasungsungan ( Ratu Ayu Lingsir and Ratu Ayu Anom ) , yangdipercayamemilikikekuatanmagis which dapatmelindungimasyarakatTista ; ( 2 ) any activity that is carried out is always through a process with the ceremony accompanying the various upakara ; ( 3 ) the culprit is the elect ( chosen girls who have not experienced puberty and is seen as a dancer who kesenengin chosen and blessed by God ) ; ( 4 ) where the play is holy places associated with yadnya ceremony at the local and pretended to be done every 210 days ( every six months in Bali or six times thirty- five days ) ; ( 5 ) the play time is the time it was considered kramat (sacred time ) and associated with yadnyadan ceremony ( 6 ) community supporters ( who believes that dance is a dance sacred Andir kesakralannya sourced from sungsungan Rangda .
Keywords: Andir dance; sacred art